Análise de confiabilidade e falhas através do fmea em motores de partida pneumáticos de motores de ciclo otto turbinados e aspirados movidos a gás natural - Lima, Hudson Magno Almeida (Universidade Federal Rural do Semi-Árido, 2018)
Due to a number of pneumatic starting motors faults used in internal combustion engines that drives reciprocating compressors in a compressor station, a study of reliability and fault analysis was required to map the problems and support decisions, which aimed to reduce the faulty rates and consequently increase the system’s reliability. For the faults mapping, the management tool Failure Mode and Effects Analysis (FMEA) was used, where actions were evaluated and prioritized based on faults modes and effects. Therefore, it was possible to develop a preventive action plan that effectively reduces the mapped faults.
Monografia
Keywords: Motor de partida pneumático; Confiabilidade; Falhas; FMEA; Ações preventivas; ENGENHARIAS::ENGENHARIA MECANICA